Learning verb phrases using a parallel corpus (Eurasian Journal of Humanities and Social Sciences, 2023)
Research on corpora and their potentials for special areas of language learning have been gaining extra attention in latest years. Albeit the utilization of corpora in language mastering and edifying is not incipient, what is novel in the present learn about is that it demonstrates for the first time the potential of a bilingual corpus in learning both grammar and translation. The paper endeavors first to define one of a kind types of corpora and concordancers, and then concentrate especially on the application of English-Uzbek parallel corpus in mastering the most possibly translations of complexified English verb phrases having no equipollent in Uzbek. It is intriguing to optically discern what options the parallel corpus would genuinely grant in such occasions. An experiment in this route reveals that the utilization of parallel corpus in translation will enhance the learners’ overall performance at least up to forty-five percent. The remaining section of the paper discusses the more than a few purposes of such corpora in exceptional areas of language studies.